Wheels steel foundation system / Dzulhannan Hakimi Zulkefle and Mohd Rofdzi Abdullah - Zulkefle, Dzulhannan Hakimi; Abdullah, Mohd Rofdzi (2023)
This study focuses on the impact of earthquakes on buildings in Malaysia. The findings reveal that earthquakes have adverse effects on the infrastructure, facilities, and overall safety of buildings such as cracking and breakage. Earthquakes can damage a building’s infrastructure and its facilities, making it to be unusable or in need of reconstruction. Therefore, this study aims to develop a system, i.e., Wheels Steel foundation system, that can be help a building to be resistant to earthquakes. The Wheels Steel foundation system design was developed from document review and data analysis. The prototype has also been tested. This research’s implications are profound, as the adoption of the Wheels Steel foundation system in buildings can significantly enhance earthquake resilience, protecting lives, and reducing reconstruction costs.